Implementation of the Philanesia Football Curriculum in View from the Medan City SSB ASKOT PSSI Training Phase - Nasution, Taufik Hidayat; Ardi Nusri; Novita, Novita (UNIB Press, 2024)
This research is to determine the implementation of the Filanesian Football Curriculum at SSB Askot PSSI Medan City. This research method is qualitative research. The informants for this research were trainers and administrators of SSB Askot PSSI Medan City. Data collection techniques in this research are through observation, documentation and interviews. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. The conclusion in this research is that the Filanesian Football Curriculum has been implemented in the Medan City PSSI Askot SSB, with details a) The training phase of the Filanesian Football Curriculum in most of the Medan City PSSI Askot SSBs is implemented differently, according to the number of students in the SSB. The conclusion in this research based on the results of data analysis and discussion, it can be seen that the SSB trainers' understanding of the Indonesian Filanesian football coaching curriculum in terms of the training phase is in the